Fostering healthy schools for students with SEND through co-production: creating an educational toolkit to support young people with 22q11.2 deletion syndrome - Gudbrandsen, Maria; Jayman, Michelle (Frontiers in Education, 2025)
Children and young people with 22q11.2 deletion syndrome (22q) face unique educational and wellbeing challenges that are often poorly understood in mainstream schools. This participatory action research (PAR) aimed to produce a practical, school-based toolkit to support the needs of pupils with 22q with a focus on wellbeing and inclusive practice. Participants included educational professionals (N = 7), young people with 22q and their parents (N = 9), and staff in schools (N = 3). Data were collected through questionnaires, a co-production workshop, and a focus group, and analyzed thematically. Participants collaboratively designed three resources; an infographic poster, a pocket guide for staff, and a short, animated video aimed at peers. Survey findings identified key gaps in staff knowledge, inconsistent provision, especially for transition, and limited wellbeing support, in line with the authors’ previous research. These findings helped to inform the development of the resources, which were praised by staff in schools for clarity, adaptability and alignment with existing practices. This study demonstrated how co-produced, low-cost resources can enhance awareness, promote inclusion and support the holistic wellbeing of pupils with 22q. This approach offers a scalable model for addressing similar gaps across wider SEND.